Optical Sensor for the Determination of Lead(II) Based On Immobilization of Dithizone onto Chitosan-Silica Membrane - Yuspian Nur; Eti Rohaeti; Latifah Kosim Darusman (Indonesian Journal of Chemistry, 2017)
Optical sensor based on incorporation of dithizone and chitosan-silica for the determination of lead (II) ion has been conducted. The optical sensor was made by composite of chitosan and silica in the ratio 2:1. Sol gel technique was chosen to make the membrane because it has some advantages such as its low temperature and chemical reactivity. The sensor has a good selectivity at pH 5 with response times at ± 180 s. Linearity responses was obtained with concentration range from 0.2 to 1.1 ppm with r2 = 0.9921. Average of %RSD on precision and accuracy (%PK) test were 1.46 and 100.96%, respectively. Limit of detection (LOD) and limit of quantification (LOQ) were 0.11 ppm and 0.37 ppm, respectively